Graphene to Advanced MoS2: A Review of Structure, Synthesis, and Optoelectronic Device Application - Tahreem Nawz; Amna Safdar; Muzammil Hussain; Dae Sung Lee; Muhammad Siyar (Crystals, 2020)
In contrast to zero-dimensional (0D), one-dimensional (1D), and even their bulk equivalents, in two-dimensional (2D) layered materials, charge carriers are confined across thickness and are empowered to move across the planes. The features of 2D structures, such as quantum confinement, high absorption coefficient, high surface-to-volume ratio, and tunable bandgap, make them an encouraging contestant in various fields such as electronics, energy storage, catalysis, etc. In this review, we provide a gentle introduction to the 2D family, then a brief description of transition metal dichalcogenides (TMDCs), mainly focusing on MoS2, followed by the crystal structure and synthesis of MoS2, and finally wet chemistry methods. Later on, applications of MoS2 in dye-sensitized, organic, and perovskite solar cells are discussed. MoS2 has impressive optoelectronic properties; due to the fact of its tunable work function, it can be used as a transport layer, buffer layer, and as an absorber layer in heterojunction solar cells. A power conversion efficiency (PCE) of 8.40% as an absorber and 13.3% as carrier transfer layer have been reported for MoS2-based organic and perovskite solar cells, respectively. Moreover, MoS2 is a potential replacement for the platinum counter electrode in dye-sensitized solar cells with a PCE of 7.50%. This review also highlights the incorporation of MoS2 in silicon-based heterostructures where graphene/MoS2/n-Si-based heterojunction solar cell devices exhibit a PCE of 11.1%.